Proposed upgrading works of NAZA Bikes showroom for NAZA Bikes Sdn. Bhd. at Lot 1, Block Two Wheel & Marine Division, Jalan 51 A/221, 46100, Petaling Jaya, Selangor Darul Ehsan / Saifudin Rahim - Rahim, Saifudin (Faculty of Architecture, Planning and Surveying, 2010)
A final year student pursuing a diploma course in Interior Design is required to prepare a final year project. The design of the project should be related closely to current issues or similar to it. The knowledge and skill acquired during the duration of the course should be put to practise and onto the drawing board. This also includes the research, case study, interviewing of clients, designing proposals, preparing art work, preparing presentation drawings, design development and last but not least the final presentation. The proposed product for this project is NAZA Bikes'. The idea to undertake this project was given due attention after taking into consideration the hardship and shortcomings encountered by a ' NAZA Bikes ' showroom in Petaling Jaya. Thereafter, a plan was proposed to prepare a premise design that may interest and fulfil the aspiration of the proprietor of the premise, owners and customers of the local vehicle. From the research and observation conducted on the product and the premise, the information and details gathered was used as a guideline to prepare the design. After scouting for a while, half of ground floor the NAZA Bikers Dream building was chosen as a proposed site for this project The objective was to design and prepare a ' NAZA Bikes ' showroom with the concept and style best suited to the business proprietor i.e. NAZA Bikes Sdn. Bhd. It is sincerely hoped that the proposed design would give the premise the desired image projection that is needed to enhanced the interest of the proprietor,' NAZA Bikes ’ owners and also enthusiasts.